Breath volatile organic compounds and inflammatory markers in adult asthma patients: negative results from the ALLIANCE cohort. Issue 2 (11th February 2021) - Holz, Olaf; Waschki, Benjamin; Watz, Henrik; Kirsten, Anne; Abdo, Mustafa; Pedersen, Frauke; Weckmann, Markus; Fuchs, Oliver; Dittrich, Anna-Maria; Hansen, Gesine; Kopp, Matthias V.; von Mutius, Erika; et al.
"Breathomics" in asthma is a rapidly growing area of significant scientific interest, as indicated by a recently published review, two research articles, and their accompanying editorials in high impact pneumology journals [1–5]. The repeatedly observed associations between breath volatile organic compounds (VOCs) and sputum or blood inflammatory cells [2, 3] suggest that breathomics are on the brink of introduction as a valuable clinically tool. However, there are also major concerns about unresolved methodological issues and a general paucity of high-quality data [1, 6]. In this letter we detail our concerns with breathomics based on data from a cohort of adult asthma patients with a broad spectrum of clinical phenotypes. Despite recent publications, we are not close to finding a clinically valuable breath VOC biomarker for asthma or asthma phenotypes https://bit.ly/3heTgtK